2005
DOI: 10.1021/jf051176t
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of Selected Flavonoids in Fruit Tissues of Various Tomato (Lycopersicon esculentumMill.) Genotypes

Abstract: Flavonoids have been studied extensively because they offer great potential health benefits. In this study, enzymatic hydrolysis of glycosylated quercetin, kaempferol, and naringin was used to obtain their sugar-free aglycones. The investigation also employed a validated HPLC method to obtain the chiral disposition of the aglycone naringenin enantiomers. These analyses were conducted on exocarp, mesocarp, and seed cavity tissues of field-grown tomato (Lycopersicon esculentum Mill.) mutants (anthocyanin absent,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 33 publications
(60 reference statements)
5
55
2
Order By: Relevance
“…3d). Consistent with previous Wndings (Torres et al 2005), hp-1 peel had the highest concentrations of all Xavonoids analysed at TU stage and a dramatic reduction of naringenin chalcone at RR stage (Fig. 3d).…”
Section: Resultssupporting
confidence: 91%
“…3d). Consistent with previous Wndings (Torres et al 2005), hp-1 peel had the highest concentrations of all Xavonoids analysed at TU stage and a dramatic reduction of naringenin chalcone at RR stage (Fig. 3d).…”
Section: Resultssupporting
confidence: 91%
“…These data are at least 1 order of magnitude higher than those commonly reported for tomato whole fruits (35,36), but several authors already reported similar levels of phenolic compounds for tomato peel (37,38).…”
Section: Effect Of Uv-b Depletion On Phenolic Biosynthesis In Peelcontrasting
confidence: 52%
“…As expected, within the cultivated species "Cherry" tomatoes showed the highest levels chlorogenic acid (23.51 mg kg −1 fw), whereas "Canario" and "Pera" tomatoes did not reach half this value (8.74 and 5.89 mg kg −1 fw respectively). Since polyphenols are mainly accumulated in the surface of tomato (Torres, Davies, Yañez, & Andrews, 2005), smaller tomatoes have higher surface to volume ratio, consequently the accumulation of polyphenols would also be higher in this type of materials. In fact, the development of new tomato varieties with outstanding functional value are targeted to the combination of high pigment (hp) genes and the restoration of anthocyanin accumulation in the fruit, specifically in "Cherry" varieties (Sestari et al, 2014).…”
Section: Quantitation Studies and Application To Real Samplesmentioning
confidence: 99%